Nghiệm của phương trình cho sau: (( (3 + i) )z + ( (4 - 5i) ) = 6 - 3i) là

Lưu lại

Nghiệm của phương trình cho sau: $\left( {3 + i} \right)z + \left( {4 - 5i} \right) = 6 - 3i$ là

Đáp án: C

$\begin{array}{l}\,\,\,\,\,\left( {3 + i} \right)z + \left( {4 - 5i} \right) = 6 - 3i\\ \Leftrightarrow \left( {3 + i} \right)z = 6 - 3i - \left( {4 - 5i} \right)\\ \Leftrightarrow \left( {3 + i} \right)z = 2 + 2i\\ \Leftrightarrow z = \frac{{2 + 2i}}{{3 + i}} = \frac{4}{5} + \frac{2}{5}i\end{array}$

Chọn C.

TOP THÀNH VIÊN NỔI BẬT

    Xem top 100 thành viên